ANALISIS PASAR MODAL DALAM TINJAUAN EKONOMI ISLAM DI UNIVERSITAS ISLAM MAJAPAHIT - Anadila Defayana Putri; Putri Nuranita Maharani Hermawan; Lia Dwi Lestari (LP2M Universitas Bina Bangsa, 2021)
This study aims to determine the capital market analysis in Islamic economic research at the Majapahit Islamic University and the effect of the capital market on student investment at the Majapahit Islamic University. The method used is a quantitative method. The method used in describing the data is through the collection of questionnaire data and observation. The results show that the capital market has an important role in increasing economic growth. Investment is one form that is sold in the capital market. Currently, the capital market is showing a lot of progress, especially with the presence of a sharia-based capital market. IDX has also collaborated with universities, one of which is GI BEI UNIVERSITAS ISLAM MAJAPAHIT as an effort to introduce the existence of the market to the younger generation. Students can start investing in several sectors, one of which is the capital market, in order to have better conditions in the future